2018
DOI: 10.5213/inj.1836050.025
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Lower Urinary Tract Symptoms in Neuromyelitis Optica in Comparison With Multiple Sclerosis Patients

Abstract: PurposeThe aim of this study was to describe lower urinary tract symptoms in neuromyelitis optica (NMO), and to compare these data with urinary disorders observed in multiple sclerosis (MS) patients.MethodsRetrospective study of data collected from January 1997 to July 2017 using the database from a Neuro-Urology Department of a university hospital. NMO and MS patients were matched for sex, age, and Expanded Disability Status Scale (EDSS)ResultsTwenty-six patients with NMO were included and compared with 33 MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…[1] Urgency, nocturia, urinary incontinence, and voiding symptoms were reported as most frequent symptoms. [1] Urinary tract infection was diagnosed in our case during hospitalization and follow-up, and it could be related to voiding symptoms. Hyponatraemia could be caused from multiple factors, and one of infamous causes being the SIADH, which could possibly be caused from disorders of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1] Urgency, nocturia, urinary incontinence, and voiding symptoms were reported as most frequent symptoms. [1] Urinary tract infection was diagnosed in our case during hospitalization and follow-up, and it could be related to voiding symptoms. Hyponatraemia could be caused from multiple factors, and one of infamous causes being the SIADH, which could possibly be caused from disorders of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…AUR is less common in women compared to men, and possible cause including neurological, anatomical, myopathic, infective, pharmacological, or functional [12] . It was reported that urinary complication was more severe in NMOSD than multiple sclerosis, and spinal injury caused by myelitis could be a reasonable explanation [1] . Urgency, nocturia, urinary incontinence, and voiding symptoms were reported as most frequent symptoms [1] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, LUTS can play a key role for the differential diagnosis of neurologic diseases that show similar symptoms, such as neuromyelitis optica (NMO) and multiple sclerosis (MS). Declemy et al [5] investigated differences in the LUTS experienced by patients between NMO and MS. NMO patients frequently experienced OAB and urinary retention, whereas low bladder compliance, serious urinary tract infections, and urinary retention were commonly observed in MS patients. As the survival rate of cancer patients is increasing, concerns about the functional changes caused by cancer treatment have emerged.…”
mentioning
confidence: 99%